Responsabilidad y Control Fiscal en los recursos Públicos: Análisis del caso de corrupción Grupo Nule (2021)
This article sets out a conceptualization and case study to identify the criteria for determining the scope and fiscal implications when a State contractor is responsible for administering public resources. This work concludes that, in practice, the process of fiscal responsibility presents difficulties in ensuring reparation for the property damage incurred, even though it is not criminal or criminal in nature. In addition, in the participation of the Tax Control Authority, in the case of study, the necessary measures were not taken despite having preventive and concomitant control powers, which as a result results in setbacks in the performance of the damage caused